Effect of resistance training on insulin resistance without clinical manifestations of type 2 diabetes in Jordanian men - Hatem A Shlool; Saleh Hammad; Abdelhafez Alnawayseh; Mohammed A Mbaydeen; Musallam N Alrosan; Muath Altarawneh; Haidar Djemai (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Resistance training has been associated with improved insulin sensitivity in individuals with type 2 diabetes, but its role in non-diabetic overweight individuals remains unclear.